Increased Incidence of Type 1 Diabetes in Children and No Change in the Age of Diagnosis and BMI-SDS at the Onset - is the Accelerator Hypothesis not Working? - Barbara Wasyl-Nawrot; Małgorzata Wójcik; Joanna Nazim; Jan Skupień; Jerzy B. Starzyk (Galenos Yayincilik, 2020)
Objective:One of the hypothesized reasons for the observed increase in type 1 diabetes incidence in children is weight gain, causing accelerated disease development in predisposed individuals. This so-called accelerator hypothesis is, however, controversial. The aim was to analyze whether, in the ethnically homogeneous population of Lesser Poland, an increase in the number of cases of diabetes among children was associated with younger age and higher body mass index-standard deviation score (BMI-SDS) at the time of diagnosis.Methods:Retrospective data analysis from medical records of all patients <14 years (n=559; 50.6% male), with newly diagnosed type 1 diabetes, in Lesser Poland between 1st January 2006 and 31st December 2017 (11 years).Results:The incidence ratio ranged significantly (p<0.001) from the lowest in 2006 (11.2/100,000/year) to the highest in 2012 (21.9/100,000/year). The mean age of diagnosis was 8.2±3.5 years. There was no trend in decreasing diagnosis age (p=0.43). The mean BMI-SDS was -0.4±1.2. Almost all children (91.6%) presented with BMI-SDS within the normal range at the time of diagnosis, with only 2.7% of cases being obese and 5.7% underweight at the moment of diagnosis. There was no clear trend at all in BMI-SDS over the study period.Conclusion:These results do not corroborate an increase of type 1 incidence in paediatric population being associated with younger age of diagnosis and higher BMI-SDS. This implies that the accelerator hypothesis does not hold true in the study population.